Unsaturated fatty acid modified bio-based nano composite coated fertilizer and preparation method thereof
By using raw materials such as unsaturated fatty acids, organosiloxanes and elolite nanotubes to prepare modified biomass nanocomposite envelope materials, the problem of insufficient hydrophobicity and density of biomass envelope fertilizers is solved, and efficient nutrient controlled release and extended release cycle are achieved.
Patent Information
- Application Number
- CN202411889635.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
The lack of hydrophobicity and density of existing bio-based envelope fertilizers leads to the release of nutrients from the fertilizer too quickly and cannot meet the growth needs of crops.
Unsaturated fatty acids, organosiloxanes and elolite nanotubes are used as raw materials, and the hydrolysis and condensation of elolite nanotubes with silicon-based fatty acid coupling agent, combined with bio-based polyols, polyester glycols and isocyanates are used to prepare semi-cured degradable bio-based polyurethanes, and the modified elolite nanotubes are loaded onto their surface. The unsaturated fatty acid modified bio-based nanocomposite envelope material is obtained by heating curing.
It improves the density and superhydrophobicity of the envelope material, significantly improves the controlled release performance of the envelope fertilizer, extends the nutrient release cycle, and meets the growth needs of crops.
Smart Images

Figure CN119707593A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coated controlled-release fertilizers, and in particular to an unsaturated fatty acid-modified bio-based nano composite coated fertilizer and a preparation method thereof. Background Art
[0002] Fertilizer is an important means of production in the agricultural planting process, and plays an important role in ensuring food security and promoting food production and income. However, unreasonable fertilization methods and blind excessive use of fertilizers lead to low nutrient utilization, which not only causes resource waste and a large loss of nutrients, but also threatens the soil environment and water resources, causing serious land non-point source pollution. Therefore, improving fertilizer utilization is of great practical significance to reducing land non-point source pollution and protecting the environment.
[0003] Coated fertilizer is an effective way and technical means to achieve efficient utilization of fertilizer nutrients. Coated urea is a material that is evenly coated on the surface of granular urea, which can slow down the release rate of fertilizer and extend the release cycle of fertilizer. Commonly used polymer coating materials are mostly petrochemical products. Although the coated fertilizer prepared by this product has good controlled release properties, the coating material is difficult to degrade in the soil, which will cause secondary pollution to the environment, and the preparation process is complicated and costly. The controlled release effect of coated fertilizers prepared from natural materials is poor and cannot meet the growth needs of crops. At present, biomass materials are also modified for the preparation of coated fertilizers. However, the bio-based polyurethane film material developed using bio-based materials has poor hydrophobicity and density, resulting in too fast nutrient release of coated controlled-release fertilizers, which cannot meet the nutrient requirements of crops. Although, modification is carried out for the poor water resistance of bio-based coating materials, for example, Chinese patent CN115043688A discloses a kind of lignin-based coated controlled release fertilizer prepared by using lignin, low polyhydroxyl value end-capped dimethylsiloxane and nano carbon black as raw materials, and the controlled release performance is improved to a certain extent. However, the organosilane used in this invention is embedded in the main chain of the polymer through the participation of active groups at both ends in the polymerization reaction, and the head and tail of the polysiloxane chain are fixed, and its migration ability is limited, and the super-hydrophobic effect cannot be achieved. We all know that the siloxane modification effect is inseparable from its surface migration ability. In addition, nano carbon black is only added to the material as a filler and is easily fixed in the polymer film. Therefore, how to improve the hydrophobicity and density of the membrane shell of the bio-based coated fertilizer still needs further research. Summary of the invention
[0004] In view of this, the object of the present invention is to provide an unsaturated fatty acid modified bio-based nanocomposite coated fertilizer and a preparation method thereof. The present invention first uses unsaturated fatty acids, organosiloxanes and halloysite nanotubes as raw materials to prepare silicon-based fatty acid modified halloysite nanotubes, uses bio-based polyols, polyester diols and isocyanates as raw materials to prepare semi-solidified degradable bio-based polyurethane, and then loads the modified halloysite nanotubes onto the surface of the semi-solidified degradable bio-based polyurethane, heats and cures, and obtains an unsaturated fatty acid modified bio-based nanocomposite coated material, the coated material has excellent compactness and surface super-hydrophobicity, and the coated fertilizer obtained after compounding with fertilizer has excellent controlled release performance.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is a method for preparing an unsaturated fatty acid modified bio-based nanocomposite coating material, comprising the following steps:
[0007] unsaturated fatty acid, organosiloxane and catalyst 1 are reacted under light conditions to obtain a silicon-based fatty acid coupling agent;
[0008] hydrolyzing and condensing the silicon-based fatty acid coupling agent and the halloysite nanotubes to obtain silicon-based fatty acid modified halloysite nanotubes;
[0009] The bio-based polyol, polyester diol and isocyanate are uniformly mixed to obtain a bio-based coating liquid, and then a reaction 2 is carried out under the action of a catalyst 2, and a semi-cured biodegradable bio-based polyurethane is obtained by controlling the reaction time of the reaction 2;
[0010] The silicon-based fatty acid-modified halloysite nanotubes are loaded on the surface of the semi-solidified bio-based polyurethane, and heated and cured to obtain the unsaturated fatty acid-modified bio-based nanocomposite coating material.
[0011] The second technical solution of the present invention is an unsaturated fatty acid modified bio-based nanocomposite coating material prepared by the above preparation method.
[0012] The third technical solution of the present invention is a coated fertilizer, which is composed of the above-mentioned unsaturated fatty acid modified bio-based nano-composite coating material and fertilizer.
[0013] A fourth technical solution of the present invention is a method for preparing the above-mentioned coated fertilizer, comprising the following steps:
[0014] The silicon-based fatty acid-modified halloysite nanotubes described in the above technical solution are uniformly dispersed in an organic solvent to obtain a silicon-based fatty acid-modified halloysite nanotube dispersion;
[0015] After the bio-based coating liquid and catalyst 2 described in the above technical solution are mixed, they are sprayed on the surface of the preheated fertilizer particles. After the bio-based coating liquid is evenly attached to the surface of the fertilizer particles, the silicon-based fatty acid modified halloysite nanotube dispersion is sprayed, heated and cured to obtain the coated fertilizer.
[0016] The present invention discloses the following technical effects:
[0017] The invention uses vegetable oil and degradable polyester diol as raw materials of coating materials to prepare coated fertilizers. The raw materials are green, renewable and degradable, thus solving the problem that the coating raw materials are non-renewable and difficult to degrade.
[0018] The present invention uses organosiloxane as a "bridge" to hydrophobically modify the nanomaterial with a long carbon chain unsaturated fatty acid to construct unsaturated fatty acid super-hydrophobic nanoparticles, which not only reduces the use of organosiloxane, but also reduces the preparation cost and avoids the disadvantage of weak super-hydrophobic stability caused by modification methods such as "dip coating".
[0019] The polyurethane synthesized by the invention has a cross-linked network structure. Vegetable oil and polyester diol react with isocyanate to form an interwoven network structure, which improves the cross-linking density and compactness of the polyurethane film material, can solve the problem of high-temperature shrinkage of pure vegetable oil-based polyurethane, and makes the surface of the coated fertilizer smoother and flatter.
[0020] The coating material provided by the present invention can effectively reduce the initial release rate of fertilizer nutrients, prolong the nutrient release cycle, and meet the growth needs of crops. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 The SEM image (a) and contact angle (b) of the film layer of the unsaturated fatty acid modified bio-based nanocomposite coated fertilizer prepared in Example 3;
[0023] Figure 2 The water contact angle of the film layer of the unsaturated fatty acid modified bio-based nanocomposite coated fertilizer prepared in Example 4;
[0024] Figure 3 The water contact angle of the film layer of the unsaturated fatty acid modified bio-based nanocomposite coated fertilizer prepared in Example 6;
[0025] Figure 4The water contact angle of the film layer of the coated fertilizer prepared in Comparative Example 2;
[0026] Figure 5 The water contact angle of the film layer of the coated fertilizer prepared in Comparative Example 3;
[0027] Figure 6 The nitrogen cumulative release rate of the coated fertilizers prepared in Examples 1-6 and Comparative Examples 1-3;
[0028] Figure 7 This is a reaction mechanism diagram for preparing unsaturated fatty acid modified bio-based nanocomposite coating materials according to the present invention. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] The first aspect of the present invention provides a method for preparing an unsaturated fatty acid modified bio-based nanocomposite coating material, comprising the following steps:
[0035] unsaturated fatty acid, organosiloxane and catalyst 1 are reacted under light conditions to obtain a silicon-based fatty acid coupling agent;
[0036] hydrolyzing and condensing the silicon-based fatty acid coupling agent and the halloysite nanotubes to obtain silicon-based fatty acid modified halloysite nanotubes;
[0037] The bio-based polyol, polyester diol and isocyanate are uniformly mixed to obtain a bio-based coating liquid, and then a reaction 2 is carried out under the action of a catalyst 2, and a semi-cured biodegradable bio-based polyurethane is obtained by controlling the reaction time of the reaction 2;
[0038] The silicon-based fatty acid-modified halloysite nanotubes are loaded on the surface of the semi-solidified bio-based polyurethane, and heated and cured to obtain the unsaturated fatty acid-modified bio-based nanocomposite coating material.
[0039] In some embodiments of the present invention, the unsaturated fatty acid is a vegetable oil containing an unsaturated bond or a derivative of a vegetable oil containing an unsaturated bond; the organosiloxane is mercaptopropyltrimethoxysilane and / or mercaptopropyltriethoxysilane; and the molar ratio of the unsaturated fatty acid to the organosiloxane is 0.5-1:0.5-3.
[0040] In some embodiments of the present invention, the unsaturated fatty acid is oleic acid, linoleic acid, linolenic acid, soybean oil, arachidonic acid, olive oil, peanut oil, walnut oil or nut oil.
[0041] In some embodiments of the present invention, the catalyst 1 is benzoin dimethyl ether; the amount of the catalyst 1 is 3% of the total mass of the unsaturated fatty acid and the organosiloxane.
[0042] In some embodiments of the present invention, the light is ultraviolet light with a wavelength of 365 nm.
[0043] In some embodiments of the present invention, the reaction time of reaction 1 is 20 to 24 hours.
[0044] In some embodiments of the present invention, the mass ratio of the silicon-based fatty acid coupling agent to the halloysite nanotubes is 3.5-5.5:4-5.
[0045] In some embodiments of the present invention, the hydrolysis condensation reaction is carried out in an alkaline alcohol solution; the alkaline alcohol solution is an ethanol solution with a pH of 9-10; the concentration of the ethanol solution is 80% v / v, 85% v / v, 90% v / v or 95% v / v. The present invention does not specifically limit the alkali solution used to adjust the alcohol solution to alkalinity, and conventional technical means of those skilled in the art can be selected, such as ammonia water.
[0046] In some embodiments of the present invention, the reaction temperature of the hydrolysis condensation is 60 to 80° C., and the reaction time is 6 to 12 hours.
[0047] In some embodiments of the present invention, the bio-based polyol is castor oil; the polyester diol is polypropylene carbonate diol, polycaprolactone diol 400 or polyester lactone 600; the isocyanate is isophorone diisocyanate, polybenzyl polyisocyanate, PM200 or 4,4-diphenylmethane diisocyanate; the catalyst 2 is dibutyltin dilaurate; the mass percentage of the polyester diol in the total of the bio-based polyol and the polyester diol is 10-30%; the molar ratio of OH in the bio-based polyol and the polyester diol to NCO in the isocyanate is 1.3-1.6:1.
[0048] In some embodiments of the present invention, the mass percentage of the polyester diol to the total mass of the bio-based polyol and the polyester diol is 15-20%.
[0049] In some embodiments of the present invention, the amount of the catalyst 2 is 0.2% of the mass of the bio-based coating liquid.
[0050] In some embodiments of the present invention, the temperature of the catalytic reaction 2 is 70-80°C.
[0051] In some embodiments of the present invention, the semi-solidified biodegradable bio-based polyurethane is obtained by controlling the reaction time of reaction 2, specifically: the reaction time of reaction 2 is controlled to be 3 to 10 minutes.
[0052] In some embodiments of the present invention, the temperature of the heating curing is 70-80° C. and the time is 10-20 min.
[0053] In some embodiments of the present invention, the amount of the silicon-based fatty acid modified halloysite nanotubes is 1% to 7% of the total solid content of the bio-based polyurethane.
[0054] The second aspect of the present invention provides an unsaturated fatty acid modified bio-based nanocomposite coating material prepared by the above preparation method.
[0055] The third aspect of the present invention provides a coated fertilizer, which is composed of the above-mentioned unsaturated fatty acid modified bio-based nano-composite coating material and fertilizer.
[0056] In some embodiments of the present invention, the fertilizer is granular urea; the particle size of the granular urea is 3 to 5 mm.
[0057] In some embodiments of the present invention, the mass ratio of the unsaturated fatty acid modified bio-based nanocomposite coating material to the fertilizer is 2.5-5:100.
[0058] A fourth aspect of the present invention provides a method for preparing the above-mentioned coated fertilizer, comprising the following steps:
[0059] The silicon-based fatty acid-modified halloysite nanotubes described in the above technical solution are uniformly dispersed in an organic solvent to obtain a silicon-based fatty acid-modified halloysite nanotube dispersion;
[0060] After the bio-based coating liquid and catalyst 2 described in the above technical solution are mixed, they are sprayed on the surface of the preheated fertilizer particles. After the bio-based coating liquid is evenly attached to the surface of the fertilizer particles, the silicon-based fatty acid modified halloysite nanotube dispersion is sprayed, heated and cured to obtain the coated fertilizer.
[0061] In some embodiments of the present invention, the organic solvent is isopropanol, anhydrous ethanol, acetone, butanone or n-hexane.
[0062] In some embodiments of the present invention, the preheating temperature is 70-80°C. In the subsequent spraying process of the bio-based coating liquid and the silicon-based fatty acid modified halloysite nanotube dispersion, the fertilizer is maintained at 70-80°C until the solidification is completed. The present invention first sprays the bio-based coating liquid and the catalyst 2 on the preheated fertilizer surface, keeps it for a certain time, so that the bio-based coating liquid is in a semi-solidified state, and then sprays the silicon-based fatty acid modified halloysite nanotube dispersion until the solidification is completed. The present invention sprays hydrophobic nanoparticles on the surface of the semi-solidified bio-based membrane so that the nanoparticles are half-wrapped and firmly fixed on the membrane surface, avoiding the traditional physical mixing that causes the particles to be completely wrapped and difficult to play a role, and solves the problem of easy falling off caused by spraying after the membrane material is completely solidified. Superhydrophobic nanoparticles can play a role stably. The nanoparticles not only increase the roughness of the membrane material, fill the pores on the surface of the membrane material, and improve the density of the membrane material, but also the long-chain alkyl chain of the unsaturated fatty acid grafted on the surface of the nanoparticles can also play a hydrophobic role.
[0063] Taking linoleic acid modified halloysite nanotubes as an example, the reaction mechanism of preparing coated fertilizers in the present invention is as follows: Figure 7 As shown in the figure, a represents the molecular formula of linoleic acid, b represents mercaptopropyltrialkoxysilane, and c represents halloysite nanotube.
[0064] All raw materials used in the examples of the present invention are commercially available.
[0065] The room temperature in the embodiments of the present invention refers to 25±2°C.
[0066] The particle size of the large granular urea in the embodiment is 3 to 5 mm.
[0067] The method for calculating the coating rate of the unsaturated fatty acid modified bio-based polyurethane coated fertilizer in the embodiment of the present invention is a weighing method. After the fertilizer and the film layer are separated, they are dried and weighed, and the mass difference before and after is calculated to calculate the actual coating rate.
[0068] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0069] Taking Example 1 as an example, the amount of oleic acid-modified halloysite nanotubes = urea mass × 0.5% × 1% = 0.05 g. The calculation method for other examples is the same.
[0070] Example 1
[0071] 28.04 g of linoleic acid, 39.26 g of mercaptopropyltrimethoxysilane and 2.02 g of benzoin dimethyl ether were irradiated under ultraviolet light (365 nm) for 24 hours to synthesize an oleic acid silane coupling agent.
[0072] 15 g of halloysite nanotubes were added to 100 mL (80% volume fraction) of ethanol solution, the pH of the solution was adjusted to 9 by adding ammonia water, the solution was ultrasonically treated for 30 min, and then 13.5 g of oleic acid silane coupling agent was added, and the reaction was maintained at 60° C. for 12 h, separated, and dried to obtain oleic acid-modified halloysite nanotubes.
[0073] 1000g of large-particle urea was put into the drum coating machine, heated by blast, and preheated at 70°C for 30min. 25g of bio-based coating liquid (14g of castor oil, 3.5g of polypropylene carbonate diol, 7.5g of isophorone diisocyanate) and 0.05g of dibutyltin dilaurate were weighed, mixed evenly, and sprayed in batches at a uniform speed into the coating pot to completely coat the fertilizer particles with the coating material. The fertilizer particles were fully dried and completely dispersed before the next coating. Spraying, each spraying amount accounts for 0.5% of the mass of urea, and a total of 5 sprayings are performed. After the last addition of the coating liquid, after 3 minutes when the coating liquid is evenly attached to the surface of the urea particles, 1% (accounting for the total mass of a single coating material) of oleic acid-modified halloysite nanotubes is dispersed in 3 mL of isopropanol solution and evenly sprayed onto the surface of the rolling fertilizer particles. The heating and curing is continued for 10 minutes, and the coating is terminated after cooling to room temperature, thereby obtaining an oleic acid-modified bio-based polyurethane coated fertilizer with a coating rate of 2.5%.
[0074] Weigh 10g coated fertilizer, pack into 100 mesh nylon mesh bag and seal, put mesh bag into solvent bottle with 200mL deionized water volume of 250mL, cover, and be placed in 25 ℃ constant temperature water bath incubator for incubation. Take samples once at intervals (sampling time is 24h, 3d, 5d, 7d, 10d, 14d, 28d, 35d, 42d, 49d, 56d, 63d, 70d, 84d). During sampling, turn the bottle upside down three times to ensure that the concentration of solution in the bottle is consistent. All the solution is taken out each time, and then an equal amount of new water is added again, and then the conductivity value of the solution is measured with a conductivity meter, and the date corresponding to the cumulative nutrient release exceeding 80% is defined as the cumulative nutrient release period of the fertilizer. The initial dissolution rate of nitrogen in the coated fertilizer obtained in the present embodiment is 11.52%, and the release period is about 21 days.
[0075] Example 2
[0076] 28.04 g of linoleic acid, 39.26 g of mercaptopropyltrimethoxysilane and 2.02 g of benzoin dimethyl ether were irradiated under ultraviolet light (365 nm) for 24 hours to synthesize an oleic acid silane coupling agent.
[0077] 15 g of halloysite nanotubes were added to 100 mL (80% volume fraction) of ethanol solution, the pH of the solution was adjusted to 9 by adding ammonia water, the solution was ultrasonically treated for 30 min, and then 13.5 g of oleic acid silane coupling agent was added, the reaction was maintained at 60° C. heating conditions for 12 h, and the solution was separated and dried to obtain oleic acid-modified halloysite nanotubes.
[0078] 1000g of large granular urea was put into the drum coating machine, heated by blast, and preheated at 70°C for 30min. 25g of bio-based coating liquid (17.5g of castor oil, 3.5g of polypropylene carbonate diol, 7.5g of isophorone diisocyanate) and 0.05g of dibutyltin dilaurate were weighed, mixed evenly, and sprayed in batches at a uniform speed into the coating pot to completely coat the fertilizer particles with the coating material. The fertilizer particles were fully dried and completely dispersed before the next coating. The coating is performed 5 times in total, with the coating amount accounting for 0.5% of the urea mass each time. After the coating liquid is added for the last time, after 3 minutes when the coating liquid is evenly attached to the surface of the urea particles, 3% (accounting for the total mass of the single coating material) of oleic acid-modified halloysite nanotubes are dispersed in 3mL of isopropanol solution and evenly sprayed on the surface of the rolling fertilizer particles. The heating and curing are continued for 10 minutes, and the coating is terminated by cooling to room temperature to obtain an oleic acid-modified bio-based polyurethane coated fertilizer with a coating rate of 2.5%. (That is, the difference from Example 1 is that the amount of oleic acid-modified halloysite nanotubes is increased from 1% to 3% (accounting for the total mass of the single coating material))
[0079] Weigh 10g coated fertilizer, pack into 100 mesh nylon mesh bag and seal, put mesh bag into solvent bottle with 200mL deionized water volume of 250mL, cover, be placed in 25 ℃ constant temperature water bath incubator and incubate. Take samples once at intervals (sampling time is 24h, 3d, 5d, 7d, 10d, 14d, 28d, 35d, 42d, 49d, 56d, 63d, 70d, 84d). During sampling, turn the bottle upside down three times to ensure that the concentration of solution in the bottle is consistent. All the solution is taken out at each time, and then an equal amount of new water is added again, and then the conductivity value of the solution is measured with a conductivity meter, and the date corresponding to the cumulative nutrient release exceeding 80% is defined as the cumulative nutrient release period of the fertilizer. The initial dissolution rate of nitrogen in the coated fertilizer obtained in the present embodiment is 6.82%, and the release period is about 28 days.
[0080] Example 3
[0081] 28.04 g of linoleic acid, 39.26 g of mercaptopropyltrimethoxysilane and 2.02 g of benzoin dimethyl ether were irradiated under ultraviolet light (365 nm) for 24 hours to synthesize an oleic acid silane coupling agent.
[0082] 15 g of halloysite nanotubes were added to 100 mL (80% volume fraction) of ethanol solution, the pH of the solution was adjusted to 9 by adding ammonia water, the solution was ultrasonically treated for 30 min, and then 13.5 g of oleic acid silane coupling agent was added, the reaction was maintained at 60° C. heating conditions for 12 h, and the solution was separated and dried to obtain oleic acid-modified halloysite nanotubes.
[0083] 1000g of large granular urea was put into the drum coating machine, heated by blast, and preheated at 70°C for 30min. 30g of bio-based coating liquid (16.8g of castor oil, 4.2g of polypropylene carbonate diol, 9g of isophorone diisocyanate) and 0.06 of dibutyltin dilaurate were weighed, mixed evenly, and sprayed in batches at a uniform speed into the coating pot to completely coat the fertilizer particles with the coating material. The fertilizer particles were fully dried and completely dispersed before the next coating. Spraying, each spraying amount accounts for 0.5% of the mass of urea, spraying 6 times in total, after the last addition of the coating liquid, after 3 minutes, the coating liquid is evenly attached to the surface of the urea particles, 1% (accounting for the total mass of the single coating material) of oleic acid-modified halloysite nanotubes are dispersed in 3mL of isopropanol solution, and evenly sprayed on the surface of the rolling fertilizer particles, and continued to heat and cure for 10 minutes, and cooled to room temperature to end the coating, and an oleic acid-modified bio-based polyurethane coated fertilizer with a coating rate of 3% is obtained. (That is, the difference from Example 1 is that 25g of bio-based coating liquid is replaced with 30g of bio-based coating liquid, which increases the amount of coating liquid.)
[0084] Weigh 10g coated fertilizer, pack into 100 mesh nylon mesh bag and seal, put mesh bag into solvent bottle with 200mL deionized water volume of 250mL, cover, be placed in 25 ℃ constant temperature water bath incubator and incubate. Take samples once at intervals (sampling time is 24h, 3d, 5d, 7d, 10d, 14d, 28d, 35d, 42d, 49d, 56d, 63d, 70d, 84d). During sampling, turn bottle upside down three times to ensure that solution concentration is consistent in bottle. All solution is taken out each time, then re-add equal amount of new water to go in, then measure the conductivity value of solution with conductivity meter, the date corresponding to more than 80% cumulative nutrient release is defined as the cumulative nutrient release period of fertilizer. The initial dissolution rate of nitrogen in the coated fertilizer obtained in the present embodiment is 2.68%, and the release period is about 28 days.
[0085] The SEM image and contact angle of the unsaturated fatty acid modified bio-based nanocomposite coating material prepared in Example 3 are shown in Figure 1 .Depend on Figure 1 It can be seen that the surface of the coated fertilizer film shell prepared according to the method of the present invention is dense and smooth, and the hydrophobicity is improved to a certain extent.
[0086] Example 4
[0087] 28.04 g of linoleic acid, 39.26 g of mercaptopropyltrimethoxysilane and 2.02 g of benzoin dimethyl ether were irradiated under ultraviolet light (365 nm) for 24 hours to synthesize an oleic acid silane coupling agent.
[0088] 15 g of halloysite nanotubes were added to 100 mL (80% volume fraction) of ethanol solution, the pH of the solution was adjusted to 9 by adding ammonia water, the solution was ultrasonically treated for 30 min, and then 13.5 g of oleic acid silane coupling agent was added, the reaction was maintained at 60° C. heating conditions for 12 h, and the solution was separated and dried to obtain oleic acid-modified halloysite nanotubes.
[0089] 1000g of large granular urea was put into the drum coating machine, and preheated at 70°C for 30min by blast heating. 30g of bio-based coating liquid (16.8g of castor oil, 4.2g of polypropylene carbonate diol, 9g of isophorone diisocyanate) and 0.06g of dibutyltin dilaurate were weighed, mixed evenly, and sprayed in batches at a uniform speed into the coating pot to completely coat the fertilizer particles with the coating material. The fertilizer particles were fully dried and completely dispersed before the next coating. The coating is performed 6 times in total, with the coating amount accounting for 0.5% of the mass of the urea each time. After the coating liquid is added for the last time, after 3 minutes, the coating liquid is evenly attached to the surface of the urea particles, 3% (accounting for the total mass of the single coating material) of oleic acid-modified halloysite nanotubes are dispersed in 3mL of isopropanol solution, and evenly sprayed on the surface of the rolling fertilizer particles, and the heating and curing are continued for 10 minutes. The coating is terminated by cooling to room temperature, and an oleic acid-modified bio-based polyurethane coated fertilizer with a coating rate of 3% is obtained. (That is, the difference from Example 2 is that 25g of bio-based coating liquid is replaced with 30g of bio-based coating liquid, which increases the amount of coating liquid.)
[0090] Weigh 10g coated fertilizer, pack into 100 mesh nylon mesh bag and seal, put mesh bag into solvent bottle with 200mL deionized water volume of 250mL, cover, and be placed in 25 ℃ constant temperature water bath incubator for incubation. Take samples once at intervals (sampling time is 24h, 3d, 5d, 7d, 10d, 14d, 28d, 35d, 42d, 49d, 56d, 63d, 70d, 84d). During sampling, turn the bottle upside down three times to ensure that the concentration of solution in the bottle is consistent. Each time, all the solution is taken out, and then an equal amount of new water is added again to go in, and then the conductivity value of the solution is measured with a conductivity meter, and the date corresponding to the cumulative nutrient release exceeding 80% is defined as the cumulative nutrient release period of the fertilizer. The initial dissolution rate of nitrogen in the coated fertilizer obtained in the present embodiment is 0.86%, and the release period is about 42 days.
[0091] Example 5
[0092] 28.04 g of linoleic acid, 39.26 g of mercaptopropyltrimethoxysilane and 2.02 g of benzoin dimethyl ether were irradiated under ultraviolet light (365 nm) for 24 hours to synthesize an oleic acid silane coupling agent.
[0093] 15 g of halloysite nanotubes were added to 100 mL (80% volume fraction) of ethanol solution, the pH of the solution was adjusted to 9 by adding ammonia water, the solution was ultrasonically treated for 30 min, and then 13.5 g of oleic acid silane coupling agent was added, the reaction was maintained at 60° C. heating conditions for 12 h, and the solution was separated and dried to obtain oleic acid-modified halloysite nanotubes.
[0094] 1000g of large granular urea was put into the drum coating machine, heated by blast, and preheated at 70°C for 30min. 40g of bio-based coating liquid (22.4g of castor oil, 5.6g of polypropylene carbonate diol, 12g of isophorone diisocyanate) and 0.08g of dibutyltin dilaurate were weighed, mixed evenly, and sprayed in batches at a uniform speed into the coating pot to completely coat the fertilizer particles with the coating material. The fertilizer particles were fully dried and completely dispersed before the next coating. The coating amount each time accounted for 0.5% of the urea mass, and the coating was sprayed 8 times in total. After the coating liquid was added for the last time, after 3 minutes when the coating liquid was evenly attached to the surface of the urea particles, 5% (accounting for the total mass of the single coating material) of oleic acid-modified halloysite nanotubes were dispersed in 3mL of isopropanol solution and evenly sprayed onto the surface of the rolling fertilizer particles. The heating and curing were continued for 10 minutes, and the coating was terminated after cooling to room temperature, thereby obtaining an oleic acid-modified bio-based polyurethane coated fertilizer with a coating rate of 4%.
[0095] Weigh 10g coated fertilizer, pack into 100 mesh nylon mesh bag and seal, put mesh bag into solvent bottle with 200mL deionized water volume of 250mL, cover, and be placed in 25 ℃ constant temperature water bath incubator for incubation. Take samples once at intervals (sampling time is 24h, 3d, 5d, 7d, 10d, 14d, 28d, 35d, 42d, 49d, 56d, 63d, 70d, 84d). During sampling, turn the bottle upside down three times to ensure that the concentration of solution in the bottle is consistent. Each time, all the solution is taken out, and then an equal amount of new water is added again to go in, and then the conductivity value of the solution is measured with a conductivity meter, and the date corresponding to the cumulative nutrient release exceeding 80% is defined as the cumulative nutrient release period of the fertilizer. The initial dissolution rate of nitrogen in the coated fertilizer obtained in the present embodiment is 0.63%, and the release period is about 56 days.
[0096] Example 6
[0097] 28.04 g of linoleic acid, 39.26 g of mercaptopropyltrimethoxysilane and 2.02 g of benzoin dimethyl ether were irradiated under ultraviolet light (365 nm) for 24 hours to synthesize an oleic acid silane coupling agent.
[0098] 15 g of halloysite nanotubes were added to 100 mL (80% volume fraction) of ethanol solution, the pH of the solution was adjusted to 9 by adding ammonia water, the solution was ultrasonically treated for 30 min, and then 13.5 g of oleic acid silane coupling agent was added, the reaction was maintained at 60° C. heating conditions for 12 h, and the solution was separated and dried to obtain oleic acid-modified halloysite nanotubes.
[0099] 1000g of large-particle urea was put into the drum coating machine, heated by blast, and preheated at 70°C for 30min. 50g of bio-based coating liquid (28g of castor oil, 7g of polypropylene carbonate diol, 15g of isophorone diisocyanate) and 0.1g of dibutyltin dilaurate were weighed, mixed evenly, and sprayed in batches at a uniform speed into the coating pot to completely coat the fertilizer particles with the coating material. The fertilizer particles were fully dried and completely dispersed for the next spraying. The spraying amount each time accounts for 0.5% of the mass of urea, and a total of 10 sprayings are performed. After the last addition of the coating liquid, after 3 minutes when the coating liquid is evenly attached to the surface of the urea particles, 5% (accounting for the total mass of a single coating material) of oleic acid-modified halloysite nanotubes are dispersed in 3 mL of isopropanol solution and evenly sprayed onto the surface of the rolling fertilizer particles. The heating and curing are continued for 10 minutes, and the coating is terminated after cooling to room temperature, thereby obtaining an oleic acid-modified bio-based polyurethane coated fertilizer with a coating rate of 5%.
[0100] Weigh 10g coated fertilizer, pack into 100 mesh nylon mesh bag and seal, put mesh bag into solvent bottle with 200mL deionized water volume of 250mL, cover, and be placed in 25 ℃ constant temperature water bath incubator for incubation. Take samples once at intervals (sampling time is 24h, 3d, 5d, 7d, 10d, 14d, 28d, 35d, 42d, 49d, 56d, 63d, 70d, 84d). During sampling, turn the bottle upside down three times to ensure that the concentration of solution in the bottle is consistent. Each time, all the solution is taken out, and then an equal amount of new water is added again, and then the conductivity value of the solution is measured with a conductivity meter, and the date corresponding to the cumulative nutrient release exceeding 80% is defined as the cumulative nutrient release period of the fertilizer. The initial dissolution rate of nitrogen in the coated fertilizer obtained in the present embodiment is 0.16%, and the release period is about 70 days.
[0101] Comparative Example 1
[0102] The only difference from Example 3 is that no modified halloysite nanotubes are added, and the remaining steps and parameters are the same as those of Example 3. The initial release rate of the fertilizer is 45.46%, and the release period is 5 days.
[0103] Comparative Example 2
[0104] The only difference from Example 3 is that the modified halloysite nanotubes are replaced by unmodified halloysite nanotubes, and the remaining steps and parameters are the same as those of Example 3. The initial release rate of the fertilizer is 30.08%, and the release period is 7 days.
[0105] Comparative Example 3
[0106] The only difference from Example 3 is that polyester diol is not added, and the remaining steps and parameters are the same as those of Example 3. The initial release rate of the fertilizer is 51.63%, and the release period is 5 days.
[0107] The water contact angles of the film layers of the coated fertilizers prepared in Comparative Examples 2 and 3 are as follows: Figure 4 (contact angle of 98.73°) and Figure 5 (Contact angle is 75.89°). Figure 1 and Figure 4 By comparison, it can be seen that when the unsaturated fatty acid modified nanoparticles are replaced with unmodified nanoparticles, although the nanoparticles increase the roughness of the membrane surface, the unmodified nanoparticles have strong hydrophilicity, so the membrane is highly hydrophilic and easy to absorb water; Figure 3 and Figure 4 By comparison, it can be seen that increasing the coating thickness and unsaturated fatty acid modified nanoparticles can significantly improve the hydrophobicity and make the membrane material super hydrophobic. By further increasing the addition amount, the cross-linking density and contact angle of the membrane material are increased, thereby improving the controlled release performance of the membrane material. Figure 5 It can be seen that the coating material that simply uses vegetable oil has low cross-linking density, loose structure, poor sealing of the coated fertilizer, and the material itself has a certain hydrophilicity, which makes it easy for water to enter the film and accelerate the dissolution and release of nutrients.
[0108] The cumulative release rate of nitrogen in different periods of the coated fertilizers prepared in the examples and comparative examples of the present application is as follows: Figure 6As shown. The release period of the unsaturated fatty acid modified bio-based nanocomposite coated fertilizer prepared in Examples 1-6 of the present invention is 21-70 days. The coated fertilizer with the corresponding controlled release period can be prepared by regulating the ratio of the materials in the coating emulsion and the coating rate to meet the nutrient requirements of different crops in the actual planting process, thereby effectively improving the fertilizer nutrient utilization rate. By comparing Examples 1 and 2, it can be seen that increasing the amount of modifier (i.e. increasing the amount of modified halloysite nanotubes) can increase the contact angle of the membrane surface and improve the hydrophobicity of the membrane. It can be seen from Examples 1 and 3 that increasing the coating rate is equivalent to increasing the coating thickness. The cross-linked network structure formed by vegetable oil and polyester diol can increase the cross-linking density of the membrane material and improve the density of the membrane material. The increase in the number of coatings further increases the density of the membrane layer. The subsequent coating can cover the previous coating to form micropores, thereby reducing the number of micropores on the surface of the membrane layer. With the same coating rate, increasing the amount of hydrophobic halloysite nanotubes added can improve the controlled release performance of the coated fertilizer. This is because the halloysite nanotubes can increase the roughness of the film layer, and the unsaturated fatty acids grafted by the nanotubes can reduce the surface energy of the film material surface, increase the hydrophobicity of the film material surface, thereby slowing down the dissolution rate and release rate of the fertilizer in the film. As can be seen from Examples 1 and 6, increasing the film thickness and the amount of hydrophobic material can effectively improve the controlled release of the coating. It is mainly due to the synergistic effect of the hydrophobicity of the hydrophobic material and the thickness of the film layer, which improves the compactness and hydrophobicity of the film material, thereby improving the controlled release of the coating. Compared with Example 3, although the comparative example 1 does not add unsaturated fatty acid to modify the halloysite nanotubes, since the film material forms an interwoven network structure through the reaction of bio-based polyols and polyester diols with isocyanates, the compactness and integrity of the film layer can be guaranteed, and the release of fertilizer can be delayed, but the delay time is short. Comparative Example 2 uses unmodified halloysite nanotubes to replace modified halloysite nanotubes. Although the halloysite nanotubes can increase the roughness of the membrane surface, due to the hydrophilicity and slow-release properties of the halloysite nanotubes, although the initial release rate of the fertilizer can be reduced to a certain extent, the release period is also short. The coated fertilizer prepared in Comparative Example 3 does not have polyester diol involved in film formation, and the polyurethane formed by vegetable oil is prone to high-temperature wrinkling, resulting in an uneven membrane shell surface and prone to forming more and larger pores. Even if hydrophobic nanoparticles are added, the nutrient release period cannot be extended.
[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an unsaturated fatty acid modified bio-based nanocomposite coating material, characterized in that: The following steps are involved: unsaturated fatty acid, organosiloxane and catalyst 1 are reacted under light conditions to obtain a silicon-based fatty acid coupling agent; hydrolyzing and condensing the silicon-based fatty acid coupling agent and the halloysite nanotubes to obtain silicon-based fatty acid modified halloysite nanotubes; The bio-based polyol, polyester diol and isocyanate are uniformly mixed to obtain a bio-based coating liquid, and then a reaction 2 is carried out under the action of a catalyst 2, and a semi-cured biodegradable bio-based polyurethane is obtained by controlling the reaction time of the reaction 2; The silicon-based fatty acid-modified halloysite nanotubes are loaded on the surface of the semi-solidified bio-based polyurethane, and heated and cured to obtain the unsaturated fatty acid-modified bio-based nanocomposite coating material.
2. The method for preparing the unsaturated fatty acid modified bio-based nanocomposite coating material according to claim 1, characterized in that: The unsaturated fatty acid is a vegetable oil containing an unsaturated bond or a derivative of a vegetable oil containing an unsaturated bond; the organic siloxane is mercaptopropyltrimethoxysilane and / or mercaptopropyltriethoxysilane; and the molar ratio of the unsaturated fatty acid to the organic siloxane is 0.5-1:0.5-3.
3. The method for preparing the unsaturated fatty acid modified bio-based nanocomposite coating material according to claim 1, characterized in that: The catalyst 1 is benzoin dimethyl ether; the amount of the catalyst 1 is 3% of the total mass of the unsaturated fatty acid and the organosiloxane.
4. The method for preparing the unsaturated fatty acid modified bio-based nanocomposite coating material according to claim 1, characterized in that: The light is ultraviolet light with a wavelength of 365nm.
5. The method for preparing the unsaturated fatty acid modified bio-based nanocomposite coating material according to claim 1, characterized in that: The mass ratio of the silicon-based fatty acid coupling agent to the halloysite nanotubes is 3.5-5.5:4-5; the reaction temperature of the hydrolysis condensation is 60-80° C., and the reaction time is 6-12 hours.
6. The method for preparing the unsaturated fatty acid modified bio-based nanocomposite coating material according to claim 1, characterized in that: The bio-based polyol is castor oil; the polyester diol is polypropylene carbonate diol, polycaprolactone diol 400 or polyester lactone 600; the isocyanate is isophorone diisocyanate, polybenzyl polyisocyanate, PM200 or 4,4-diphenylmethane diisocyanate; the catalyst 2 is dibutyltin dilaurate; the mass percentage of the polyester diol in the total of the bio-based polyol and the polyester diol is 10-30%; the molar ratio of OH in the bio-based polyol and the polyester diol to NCO in the isocyanate is 1.3-1.6:
1.
7. The method for preparing the unsaturated fatty acid modified bio-based nanocomposite coating material according to claim 1, characterized in that: The temperature of the catalytic reaction 2 is 70-80° C.; the temperature of the heating curing is 70-80° C., and the time is 10-20 minutes.
8. An unsaturated fatty acid modified bio-based nanocomposite coating material prepared by the preparation method according to any one of claims 1 to 7.
9. A coated fertilizer, characterized in that: The invention is composed of the unsaturated fatty acid modified bio-based nanocomposite coating material according to claim 9 and fertilizer.
10. A method for preparing the coated fertilizer according to claim 9, characterized in that: The following steps are involved: The silicon-based fatty acid-modified halloysite nanotubes of claim 1 are uniformly dispersed in an organic solvent to obtain a silicon-based fatty acid-modified halloysite nanotube dispersion; The bio-based coating liquid and catalyst 2 in claim 1 are mixed and sprayed on the surface of the preheated fertilizer particles. After the bio-based coating liquid is evenly attached to the surface of the fertilizer particles, the silicon-based fatty acid modified halloysite nanotube dispersion is sprayed, heated and cured to obtain the coated fertilizer.
Citation Information
Patent Citations
Organic silicon modified activated lignin-based coating material, preparation method thereof and coated fertilizer
CN115043688A
Cited By
Preparation method of large-particle urea surface treatment liquid and application of large-particle urea surface treatment liquid in polyurethane coating
CN121850801A